Research on continuous monitoring of cloud computing service - Xing-shu CHEN,Long GE,Yong-gang LUO,Xiang LI (网络与信息安全学报, 2016)
The complexity and dynamism of cloud computing environment hardly lead to timely awareness of cloud computing service’s operating state and assessment of cloud computing service risk.In order to ensure that the security of cloud service abidingly conforms to relevant national standard,continuous monitoring of cloud computing service was researched,and the role of cloud service provider was defined,customer,and continuous monitoring,described their supervising responsibility,and assessed index system and interface specification,thus guaranteeing stable and secure employment of cloud computing service by government department and key industries.